Cognitive Weighted Polymorphism Factor: Empirical and Theoretical Validations (International Journal of Engineering and Computer Science, 2017)
Software complexity metrics are valuable and widely accepted tools to produce high quality software. The quality of the software metrics depends on various validations to prove it as valid, robust, realistic, accurate, and comprehensive metric. So, validations are important while proposing a new complexity metric. The Cognitive Weighted Polymorphism Factor complexity metric, already proposed by the author, is validated empirically as well as theoretically to prove its worth. Case studies are conducted to prove the applicability of the metric in all situations. To show the theoretical soundness of the metric, validations are done against Weyuker’s nine properties and Abreu’s seven criteria. The empirical validation is done to corroborate the theoretical validations. To show the better accuracy of the metric, the comparative study is done. Finally, the statistical validity is displayed with the performance of correlation analysis. All the validations proved that the Cognitive Weighted Polymorphism Factor complexity metric is truly a valid, more robust, more realistic, more accurate and more comprehensive in nature.